in Search of Leaders with Chinesecharacteristics: A Reflection of Indonesia's 2014 General Election - Dahana, Abdullah; Rosalin, Kelly; Wiannastiti, Melani (Bina Nusantara University, 2016)
Article dealt with the questions of leadership transition in post–Mao Zedong/Deng Xiaoping era. During the time of Mao and Deng, factionalism played important roles in all segments of Chinese politics, including the election of a leader. After Mao and Deng, although factionalism persisted, it did not become contradiction, but rather it created a situation in which factions within the Chinese Communist Party (CCP) cooperated in all aspects of Chinese politics. The main objective of this research was the perpetuation of the party’s grip on political power . The article also dealt with the questions of recruiting and educating party cadres. Career paths of three post-Deng Chinese leaders, i.e., Jiang Zemin, Hu Jintao, and Xi Jinping were also explored to explain the period they reached their peak of their careers by blood and sweat. This article finds that it cannot be denied that what is happening in China now in the area of leadership is using a system of a political dynasty.